Photocatalytic activity and reusability of ZnO layer synthesised by electrolysis, hydrogen peroxide and heat treatment. Issue 15 (2nd August 2016) - Akhmal Saadon, Syaiful; Sathishkumar, Palanivel; Mohd Yusoff, Abdull Rahim; Hakim Wirzal, Mohd Dzul; Rahmalan, Muhammad Taufiq; Nur, Hadi
ABSTRACT: In this study, the zinc oxide (ZnO) layer was synthesised on the surface of Zn plates by three different techniques, i.e. electrolysis, hydrogen peroxide and heat treatment. The synthesised ZnO layers were characterised using scanning electron microscopy, X-ray diffraction, UV–visible diffuse reflectance and photoluminescence spectroscopy. The photocatalytic activity of the ZnO layer was further assessed against methylene blue (MB) degradation under UV irradiation. The photocatalytic degradation of MB was achieved up to 84%, 79% and 65% within 1 h for ZnO layers synthesised by electrolysis, heat and hydrogen peroxide treatment, respectively. The reusability results show that electrolysis and heat-treated ZnO layers have considerable photocatalytic stability. Furthermore, the results confirmed that the photocatalytic efficiency of ZnO was directly associated with the thickness and enlarged surface area of the layer. Finally, this study proved that the ZnO layers synthesised by electrolysis and heat treatment had shown better operational stability and reusability.